2013
DOI: 10.4062/biomolther.2013.044
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin Inhibits LPS-Induced Macrophage Activation by Blocking p38 MAPK in RAW 264.7 Cells

Abstract: We demonstrate herein that silibinin, a polyphenolic flavonoid compound isolated from milk thistle (Silybum marianum), inhibits LPS-induced activation of macrophages and production of nitric oxide (NO) in RAW 264.7 cells. Western blot analysis showed silibinin inhibits iNOS gene expression. RT-PCR showed that silibinin inhibits iNOS, TNF-α, and IL1β. We also showed that silibinin strongly inhibits p38 MAPK phosphorylation, whereas the ERK1/2 and JNK pathways are not inhibited. The p38 MAPK inhibitor abrogated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 35 publications
3
34
1
1
Order By: Relevance
“…These results suggest that phosphorylation of p38 MAPK is involved in the inhibitory effects of CTB on LPS-induced inflammatory gene expression. Next, we moved forward to test the activation of phosphorylations of MKK3/6, which are two closely related kinases that phosphorylate p38 at its Thr-Gly-Tyr site [47]. As shown in Figure 5D, the increased phosphorylation of MKK3/6 induced by LPS was suppressed by CTB in a dose-dependent manner, but that this did not affect the total amount of MKK3/6.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that phosphorylation of p38 MAPK is involved in the inhibitory effects of CTB on LPS-induced inflammatory gene expression. Next, we moved forward to test the activation of phosphorylations of MKK3/6, which are two closely related kinases that phosphorylate p38 at its Thr-Gly-Tyr site [47]. As shown in Figure 5D, the increased phosphorylation of MKK3/6 induced by LPS was suppressed by CTB in a dose-dependent manner, but that this did not affect the total amount of MKK3/6.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies also demonstrated that silybin possessed anti-inflammatory properties (Al-Anati et al, 2009;Chittezhath et al, 2008;Giorgi et al, 2012;Gu et al, 2007;Kim et al, 2012;Prabu and Muthumani, 2012;Salamone et al, 2012;Youn et al, 2013). Therefore, silybin might be a suitable protective agent for early diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 94%
“…Specific primers for TGF-1 (sense 5′-TTG CTT CAG CTC CAC AGA GA-3′, antisense 5′-TGG TTG TAG AGG GCA AGG AC-3′), IL-4 (sense 5′-ACG GAG ATG GAT GTG CCA AAC-3′, antisense 5′-AGC ACC TTG GAA GCC CTA CAG A), and IL-13 (sense 5′-CGG CAG CAT GGT ATG GAG TG-3′, antisense 5′-ATT GCA ATT GGA GAT GTT GGT CAG-3′) were used to amplify gene fragments. PCR was performed over 27 cycles of denaturation at 95 o C for 30 s, annealing at 52 o C for 30 s, and elongation at 72 o C for 30 s in an Eppendorf Mastcycler PCR machine (Hamburg, Germany)(Youn et al, 2013). Specific primers for GAPDH (sense 5′-TTC ACC ACC ATG GAG AAG GC-3′, antisense 5′-GGC ATG GAC TGT GGT CAT GA-3′) were used and annealing was undertaken at 60°C.…”
mentioning
confidence: 99%